Application of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders in a Group Format for Adults: A Scoping Review Protocol - Machiko Kajiwara; Noriko Kato; Motohiro Nishiuchi; Hiroko Fujisato; Kyousuke Kaneko; Hironori Kuga; Masaya Ito (Behavioral Sciences)
The group format of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders (UP) shows promise as a efficient method for delivering established and effective psychological treatments for emotional disorders. The implementation of psychological treatment in a group format varies according to a country’s local circumstances, policies, and culture. To date, there are no comprehensive reviews of aspects related to settings, participants, providers, and interventions for applying the UP in a group context. Therefore, we have prepared a scoping review protocol to clarify the fields, participant characteristics, intervention structures, and therapist training methods related to group-format UP, aiming to facilitate its implementation across diverse regions and contexts. Based on this protocol, the scoping review will follow the Joanna Institute guidelines and PRISMA statement extensions for scoping reviews. The review will include studies of the group format of UP that describe symptoms of emotional disorders in adults. The following databases will be searched: PubMed, MEDLINE, Web of Science, PsycINFO, and ClinicalTrials.gov. The selected data will be organized according to four predefined research questions. This scoping review will provide suggestions to promote the application and implementation of the UP in a group format and contribute to disseminating evidence-based psychological treatment.